Resurgence of influenza A after SARS-CoV-2 omicron wave and comparative analysis of hospitalized children with COVID-19 and influenza A virus infection - Lin, Fen; Chen, Man-Tong; Zhang, Lin; Wu, Min; Xie, He; Guan, Ze-Xiang; Yang, Zhe; Cai, Zhong-Xian; Wen, Jin-Zhou; Yang, Li-Ye (Frontiers in Medicine, 2024)
The highly infectious Omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have caused large-scale transmission from Dec 2022 to Feb 2023 in China. After this event, a remarkable surge of influenza A (Flu A) occurred from March to May 2023, especially in pediatric patients.This study aimed to investigate the differences between pediatric patients infected with COVID-19 Omicron and Flu A virus.A total of 1063 hospitalized children who admitted into two tertiary general hospital of Guangdong province of China were included. Medical records were compared retrospectively in these patients during the epidemic periods of SARS-CoV-2 omicron and Flu A.592 Patients with Flu A were mostly preschool and school-aged (>3y, 76.0%), they showed higher ratio of high fever (≥39℃) and fever duration (≥5 days), cough, rhinorrhea and vomiting compared to patients with SARS-CoV-2 omicron. Most of the 471 Omicron patients were young children (0-3y, 74.5%) and had more poor appetite and dyspnea symptom. Benign acute children myositis (BACM) was only observed in patients with Flu A, and a significant male predominance. Multisystem inflammatory syndrome in children (MIS-C) was only found in patients with SARS-CoV-2 Omicron. Compared to the SARS-CoV-2 Omicron group, the Flu A group showed reduced lymphocyte (Lym) and platelet (PLT) counts, and elevated levels of aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and creatinine kinase-MB (CK-MB) in laboratory indexes (P<0.05). Additionally, it was found that more children hospitalized with COVID-19 had increased C-reactive protein (CRP) levels compared to those with Flu A (P<0.05).Influenza A infections have notably surged in children, coinciding with the relaxation of COVID-19 related social restrictions. During the epidemic periods of Omicron and Flu A virus infection, different clinical and laboratory characteristics were observed in hospitalized children.